Plant Variety Protection, Farmers’ Rights, and Agrarian Justice: An Islamic Socio-Legal Perspective on Agricultural Capitalization in Indonesia - Rheyna Hanny Laurencya; Ria Wierma Putri; Kasmawati Kasmawati (Journal of Indonesian Islamic Studies, 2026)
The capitalization of the agricultural sector has transformed seed governance from community-based agricultural practices into industrial systems dominated by corporate interests and intellectual property regimes. In Indonesia, the implementation of Plant Variety Protection (PVP) under Law Number 29 of 2000 has generated significant challenges regarding farmers’ rights, local seed sustainability, and agrarian justice. This study aims to analyze the impact of agricultural capitalization on farmers’ rights and local seed systems, as well as to evaluate the implementation of the PVP regime from an Islamic socio-legal perspective. This research employs a normative-empirical legal method using an Islamic socio-legal approach. Primary legal materials consist of national and international regulations concerning plant variety protection, while secondary materials include scholarly literature, policy reports, and previous studies related to agricultural capitalization and seed governance. The findings indicate that the implementation of the PVP system remains dominated by corporations and formal research institutions, while smallholder farmers face structural barriers in accessing legal protection. Technical requirements, administrative complexity, and unequal institutional access contribute to the marginalization of traditional seed systems and increase farmers’ dependency on commercial seed markets. From an Islamic socio-legal perspective, the concentration of control over seeds raises concerns regarding distributive justice, public welfare (maṣlaḥah), and monopolistic practices (iḥtikār). This study argues that Indonesia’s PVP system requires substantial reform through a more inclusive legal framework that recognizes farmers’ rights, protects local seed systems, and balances innovation incentives with social justice and collective welfare.